A measurement method for capacitive sensors based on a versatile direct sensor-to-microcontroller interface circuit. (April 2020) - Czaja, Zbigniew
Graphical abstract: Highlights: A new time-domain measurement method for capacitive sensors is proposed. A simple versatile direct sensor-to-microcontroller interface circuit is used. The method is designed to capacitive relative humidity sensors. The method is for microcontrollers with internal ACs and precise reference voltages. Very good experimental results were obtained (the relative errors less than ±0.06%). Abstract: In the paper, there is presented a new time-domain measurement method for determining the capacitance values of capacitive sensors, dedicated, among others, to capacitive relative humidity sensors. The method is based on a versatile direct sensor-to-microcontroller interface for microcontrollers with internal analog comparators (ACs) and with precision voltage reference sources, e.g. digital-to-analog converters (DACs). The reference source can be replaced by a resistive divider attached to the negative input of the AC. The interface circuit consists only of a reference resistor Rr, a given capacitive sensor working as a voltage divider, and a microcontroller (its peripherals: AC, timer, DAC, I/O pins). A prototype of the proposed complete solution of a compact capacitive smart sensor based on an 8-bit ATXmega32A4 microcontroller has been developed and tested. The maximum possible relative inaccuracy of an indirectly measurable capacitance was analysed, and experimental research was also performed. The results confirmed that the relative errors of value determination for a capacitive sensor are less than ±0.06%, which corresponds to a capacitance measurement accuracy of less than 0.1 pF for a range of measured capacity values from 100 pF to 225 pF, which in turn corresponds to at least a 0.5% relative humidity resolution for commercial capacitive RH sensors (e.g. TE Connectivity HS1101LF and Philips H1).